Strengthening India’s tuber crops research network: AICRP on tuber crops - Sreekumar, J; Kumar, H Kesava; Byju, G (Indian Horticulture, 2025)
Under the umbrella of ICAR, All India Coordinated Research Project (AICRP) on Tuber Crops links 21 centres across 18 states to improve cassava, sweet potato, taro, yams, and crops. The network conserves 4,448 accessions, has recommended 152 varieties, and released 100 for diverse agro-ecologies. It standardizes region specific agronomy, precision nutrient and water management, and IPM/IDM, while popularizing value-addition and enterprises. Decentralized seed systems produced millions of cassava stems and sweet potato vines, plus tonnages of aroids and yams, accelerating varietal adoption. Priorities include climate-ready genetics, clean seed economies, precision management, community-scale IPM, and market integration to close yield gaps, enhance resilience, and drive growth.